Electrical installation work - Scaddan, Brian (Newnes, 2011)
Brian Scaddan's Electrical Installation Work explains in detail how and why electrical installations are designed, installed and tested. You will be guided in a logical, topic by topic progression through all the areas required to complete the City and Guilds 2357 Diploma in Electrotechnical Technology. Rather than following the order of the syllabus, this approach will make it easy to quickly find and learn all you need to know about individual topics and will make it an invaluable resource after you've completed your course. With a wealth of colour pictures, clear layout, and numerous diagrams and figures providing visual illustration, mastering difficult concepts will be a breeze. This new edition is closely mapped to the new City and Guilds 2357 Diploma and includes a mapping grid to its learning outcomes. It is also fully aligned to the 17th Edition Wiring Regulations. Electrical Installation Work is an indispensable resource for electrical trainees of all ability levels, both during their training and once qualified. Brian Scaddan, I Eng, MIET, is a consultant for and an Honorary Member of City and Guilds. He has over 35 years' experience in Further Education and training. He is Director of Brian Scaddan Associates Ltd, an approved City and Guilds and NICEIC training centre offering courses on all aspects of Electrical Installation Contracting including the City and Guilds 2382, 2391, 2392, 2377 series and NICEIC DISQ courses. He is also a leading author of books on electrical installation.